Design of nonblocking high-density photonic switches - Mohamed Suliman, Fakher Eldin (2004)
Crosstalk, signal attenuation, and nonblocking type are considered the most critical issues that limit the switch density in photonic switches. The research is a theoretical study to develop high-density photonic switch architectures with reduced crosstalk and attenuation and improved nonblocking performance. Four photonic switching networks have been proposed based on lithium niobate (LiNbO3) directional couplers. They are called NWN, NSN, SCS, and NMN networks. Ideas from the theory of circuit switching have been considered and space dilation techniques have been adopted using new approaches. The properties of the proposed networks have been examined and formulated. Comparison with other well-known designs has also been presented and analyzed. All proposed networks suit unicast connections with the NMN network also capable of multicasting. The NWN is nonblocking in the wide sense while the others are strictly nonblocking. The optimum switch dimension for the proposed networks was found to be 16. With this size the insertion loss of the NWN, NSN, SCS, and NMN networks is 17, 17, 15, and 21 dB, respectively. This signal attenuation is lower than the constraint of 30 dB beyond which optical amplifiers may be needed. The respective signal-to-noise ratio with this size is 11.549, 11.549, 20, and 13.979 dB, which is also higher than the 11 dB required for achieving a good bit error rate performance. The penalty to achieve these results is more hardware complexity that is reflected by the number of couplers used and the number of waveguide crossovers required. Waveguide crossovers can, however, be reduced if some stages or subnetworks of the switch are fabricated on separate substrates.